New insights into the development of regional unemployment disparities - Daniel Werner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Large regional unemployment disparities are a common feature of the labor market in many countries. This study deals with the question whether regional unemployment disparities in western Germany widen, become narrower or remain constant over time. It examines the hypothesis of convergence for regional unemployment rates of western German Federal States and the time period 1968 to 2009 following different concepts of convergence. Western German regional unemployment rates exhibit beta-convergence but no sigma-convergence. Further, regional unemployment rates show a high degree of intra-distributional dynamics. Panel unit root tests designed for cross-sectional dependent panels are applied to investigate the hypothesis of stochastic convergence. This is necessary because the assumption of cross-sectional independency does not hold. The results do not indicate the existence of stochastic convergence. This is in contrast to previous studies that do not take cross-sectional dependence into account. However, additional robustness checks show that evidence of stochastic convergence depends on the underlying assumption about the shape of the equilibrium relationship between regional unemployment rates and their national counterpart. Western German regional unemployment is not characterized by a catching-up process between high and low unemployment regions. The development of regional unemployment disparities is mainly driven by economic disturbances.
Keywords: C33; J60; R12; 330